(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2022)
This article is devoted to describe the psychological and behavioral influence of children’s fiction to the upbringing of a child. “The Chronicles of Narnia” was selected as a bright example of upbringing child’s psychological and moral world. We can see some quotes or scenes taken from this novel, in which children can obtain the priceless knowledge.